PERLINDUNGAN HUKUM BAGI KONSUMEN YANG MENERIMA UANG KEMBALIAN DALAM BENTUK BARANG ATAU PERMEN: Legal Protection For Consumers Who Receive Change Money In The Form Of Goods Or Candies - Chandra, Shyerla; Lestari, Suci (Faculty of Law, Universitas Trisakti, 2024)
This research was conducted at Shop X in Tanjung Pendam Village, Belitung Regency, which gives candies or goods, as change money of their consumers’ bill. The problem in this article is what’s the reason of shop X gives candies or goods as change money? and does this violates the Consumer Protection Law? And what kind of legal efforts for the consumers who receive candies or goods as change money according to the Consumer Protection Law and related regulations? The first conclusion is that Shop X using candies or goods as change money because it has runout of small change or coins and this violates Article 4 Section (a), (d), (g) and Article 7 Section(a), (c) Consumer Protection Law. Second, the legal efforts that the consumers can submit a complaint to the store manager and if no response is received, then they make a complaint to the National Consumer Protection Agency and settle disputes through the Consumer Dispute Settlement. Consumers must be smart to know and understand theirs rights and taking the right steps and business owners must prepare sufficient coins for change money.